Słowo i obraz wychowuje. Wybór książek o tematyce patriotycznej z przełomu XIX i XX w. adresowanych do dzieci - Boguszewska, Anna (Biuletyn Historii Wychowania, 2026)
The aim of the article is to reconstruct a selection of historical books that were the strict basis for use in the patriotic upbringing of children at the turn of the 19th and 20th centuries in Poland. In shaping patriotic attitudes, especially towards the youngest, the stories learned in specially prepared educational books and the transmission of legends were used. In the second half of century, these topics were popularized by: W.L. Anczyc, W. Bełza, Z. Bukowiecka, M. Ilnicka, A. Gawiński, J. Laskorys, W. Przyborowski, H. Radlińska, Z. Węgierska. The subject of the research does not include books on nature, fairy tales or social topics. The chronological and problem arrangement has been preserved. Elements of the monographic method, document analysis technique and content analysis method used in qualitative research were used.